Problems after flight: understanding and comparing Syrians' perspectives in the Middle East and Europe - Andrea Drescher; Nikolai Kiselev; Aemal Akhtar; Ceren Acarturk; Richard A. Bryant; Zeynep Ilkkursun; Roland von Känel; Kenneth E. Miller; Monique C. Pfaltz; Matthis Schick; Ulrich Schnyder; Marit Sijbrandij; et al. (BMC, 2021)
Abstract Background Syrian refugees and asylum seekers (SRAs) face multiple stressors after flight, which may vary due to different geographic, economic, cultural and socio-political contexts in the host countries. Past research has recognised the importance of participants' own perspectives. The aims of this multi-country study were to identify and compare self-reported problems of SRAs between various settings. Methods A semi-structured client-generated outcome measurement was used to collect data among adult SRAs in Jordan (N = 61), Turkey (N = 46) and Switzerland (N = 57) between September 2018 and November 2019. Answers were analysed following thematic analysis. Results Over half of the participants reported practical problems with an emphasis on camp-related problems (Jordan), finances (Turkey), employment (Jordan and Switzerland) and government regulations (Switzerland), followed by psychological, and social issues. Conclusion This study highlights the impact of local contextual factors on wellbeing. The findings emphasise that planning preventative procedures and mental health care services for SRAs need to consider local challenges affecting the population in specific countries.